(untitled) (Bangladesh Journal of Medical Education, 2017)
This cross-sectional study was conducted to find out the views of some stakeholders in regarding the current quality assurance activities in different government and non-government dental institutions of Bangladesh. Students, intern doctors, teachers and head of the institutions were the respondents. Semi-structured self-administered questionnaire, interview schedules and a checklist were used for data collection. The sampling technique was convenience and purposive. The study was conducted in 2015 and 2016. The study revealed that teachers were satisfied with the overall educational environment, but students are not certain about this mater and the students’ opinion were negative in regards to hostel and library facilities. Only few teachers were engaged in research activities in which authorities do not provide any assistance. Almost all dental institutions are deficient in their quality assurance activities. Other than academic council most of the quality assurance bodies are absent or non-functioning. The study recommends that quality assurance activities in undergraduate dental institutions in Bangladesh should be strengthened and it should be evaluated by the national quality assurance body. Bangladesh Journal of Medical Education Vol.8(2) 2017: 7-11